2020
DOI: 10.1007/s40520-020-01592-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical response of the upper body to unexpected perturbations during gait initiation in young and older adults

Abstract: Background: Control of upper body motion deteriorates with ageing leading to impaired ability to preserve balance during gait, but little is known on the contribution of the upper body to preserve balance in response to unexpected perturbations during locomotor transitions, such as gait initiation.Aim: To investigate differences between young and older adults in the ability to modify the trunk kinematics and muscle activity following unexpected waist lateral perturbations during gait initiation.Methods: Ten yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Instead, Maslivec et al ( 2018 ) reported a bilateral excitation in sternocleidomastoid and ES muscles (at T9 and L3 level), again after the backward CoP shift, with a larger delay in sternocleidomastoid in older subjects. The bilateral activation of cervical and thoracic ES in elder subjects is appreciable also in the study by Rum et al ( 2021 ), again about 200 ms after the CoP shift. Wang et al ( 2005 , 2006 , 2017 ) dedicated several studies to this topic.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Instead, Maslivec et al ( 2018 ) reported a bilateral excitation in sternocleidomastoid and ES muscles (at T9 and L3 level), again after the backward CoP shift, with a larger delay in sternocleidomastoid in older subjects. The bilateral activation of cervical and thoracic ES in elder subjects is appreciable also in the study by Rum et al ( 2021 ), again about 200 ms after the CoP shift. Wang et al ( 2005 , 2006 , 2017 ) dedicated several studies to this topic.…”
Section: Discussionsupporting
confidence: 72%
“…So far, only a few studies have searched for activities in trunk muscles linked to gait initiation. Despite the recordings reported in some of those studies (Assaiante et al, 2000 ; Wang et al, 2005 , 2017 ; Ceccato et al, 2009 ; Rum et al, 2021 ) encompassed the initial backward shift of CoP, no description was provided for EMG activities preceding such shift, while changes occurring between CoP shift and heel-off were systematically reported. Assaiante et al ( 2000 ) studied the development of postural chains in children, showing an excitation occurring in both extensor and flexor muscles of the trunk, only on the swing side, about 200 ms before heel-off, i.e., 300 ms after the CoP shift.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the tested population, perturbations of different natures have been used, ranging from cognitive [10] to visual [11] and physical [12]. At the same time, several variables have been considered as sensitive for the quantification of human responses to gait perturbation; among other, spatio-temporal parameters [13], dynamic stability [13][14][15][16], muscular activity [12,17,18], kinematics [14,16,18], and inter-joint coordination [3,19] have been the most adopted ones.…”
Section: Introductionmentioning
confidence: 99%
“…Moving to kinematics, the analysis of trunk and upper body segments was deeply conducted in previous studies. As an example, Rum and colleagues [18] quantified the trunk kinematic differences between young and older healthy adults following unexpected waist lateral perturbation during walking. A reduction in trunk movement was found as a significant effect of the aging, underlying a more rigid behavior of the upper body in older adults when they are asked to respond to unexpected perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Most perturbations were applied through a translation of the support surface (14 studies), either in the mediolateral or anteroposterior direction, or both. The other types of perturbations were waist-pulls [ 43 , 67 ], ankle pull [ 9 , 50 ], tripping [ 63 ], visual perturbations [ 40 , 75 ], soapy water [ 44 ] and surface drop [ 37 ].…”
Section: Resultsmentioning
confidence: 99%